A Different Perspective on Garden Grabbing. Mapping the Adaptive Capacity of Home Food Production. - Dewaelheyns, Valerie; Lerouge, Frederik; Rogge, Elke; Vranken, Liesbet (My University, 2015)
Current trends in urban development strive for the densification of existing urban areas. This densification can be operationalized by the decrease and intake of domestic garden area. Yet, such densification projects may result in potential losses with regards to the support of ecosystem services and the safeguarding of urban adaptive capacity. The manifold of multifunctional garden spaces present worldwide offers for example interesting perspectives for food provisioning. By developing a theoretical model to capture, quantify and interrelate the most relevant variables and constraints of potential food production in domestic gardens, insight is gained in the food production potential of domestic gardens. Also the influence of utility on the household's decision on how much space and time to devote to food production was incorporated. The model development was fostered by quantitative and qualitative data collection for the case study Flanders. These data allowed to gain insights in the current food production and potential for food production in Flemish domestic gardens. Such insights allow the exploration of spatial and temporal constraints of individual domestic gardens for food production. This contributes to a better understanding of the adaptive capacity of garden space interwoven within the urban fabric. As such, the qualities and potentials enclosed within the existing garden area can be put next to the benefits of building these areas. Moreover, insights are gained in points of attention when private garden areas would be addressed for food provisioning.
Keywords: Stadtentwicklung; Verdichtung; Gartenbau; Lebensmittelproduktion; Urban Gardening; Hausgarten; Datenanalyse; Fallstudie